Partial Substitution of Fish Meal with Petek (Leiougnathus equulus) Flour in Commercial Feed of Patin Siam (Pangasius hypopthalamus) Fry - Oktavianti, Dian; Santoso, Limin; Suparmono, Suparmono (Jurusan Perikanan dan Kelautan, 2015)
Patin Siam (Pangasius hypopthalamus) is a freshwater fish which is received considerable attention by public and has high economic value. In process of cultivation, farmers often got problems because of high price of feed. It’s because raw materials feed such fish meal still import from another country. One of the efforts to reduce the use of imported fish meal is using Petek fish meal. The aim of this research was to determine the effect of the use of Petek fishmeal as partial substitution of fish meal. This research used Completely Randomized Design (CRD) with 5 treatments and 3 replications namely treatment A (commercial pellets / control), B (fish meal 75% + Petek fish meal 25%), C: (fish meal 50% + Petek fish meal 50%), D (25% fish meal + 75% Petek fish meal) and E: (0% fish meal + Petek fish meal 100%). Observed variables were absolute growth, daily growth rate, survival rate, and feed conversion ratio (FCR). Data were analyzed by ANOVA and Duncan test. The tested fish were cultivated in aquarium with dimension of 60 x 40 x 40 cm3 for 50 days. Fishes were feed three times a days with feeding rate of 5%. The results showed that the use of Petek fishmeal in feed could increase absolute growth and daily growth rate. The treatment of C resulted in highest absolute growth of Patin Siam and lowest feed conversion ratio. The treatments did not effect the survival rate of Patin Siam.